2012
DOI: 10.1016/j.anr.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and Religious Death Practices in Western Turkey

Abstract: We recommended that nurses and physicians be closely acquainted with the prevailing traditions and religious beliefs in the communities where they served.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 2 publications
2
28
0
3
Order By: Relevance
“…The lowest score for nutrition subscale is 9.0 and the highest score is 36.0; the lowest score for physical activity subscale is 8.0 and the highest score is 32.0. Higher scores indicate a healthier lifestyle [ 23 , 24 ]. In this study, the scale which was developed by Walker et al, [ 23 ] and whose Turkish validity and reliability was conducted by Bahar et al, [ 24 ] was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lowest score for nutrition subscale is 9.0 and the highest score is 36.0; the lowest score for physical activity subscale is 8.0 and the highest score is 32.0. Higher scores indicate a healthier lifestyle [ 23 , 24 ]. In this study, the scale which was developed by Walker et al, [ 23 ] and whose Turkish validity and reliability was conducted by Bahar et al, [ 24 ] was used.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate a healthier lifestyle [ 23 , 24 ]. In this study, the scale which was developed by Walker et al, [ 23 ] and whose Turkish validity and reliability was conducted by Bahar et al, [ 24 ] was used. General alpha value of the scale was found as 0.92 by Bahar et al [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although death is described as a natural process of the life cycle and an inevitable reality of life, it is typically one of the most painful experiences of loss undergone by the patient and his/her family (Cimete, ). Nurses’ knowledge about the dying patient and his/her family's sociocultural status will play a key role in designating the type of care strategies to be implemented (Bahar, Beser, Ersin, Kissal, & Aydogdu, ; İnci & Oz, ). It is everybody's right to receive a holistic and sensitive care from the medical staff.…”
mentioning
confidence: 99%
“…Many researchers recommend that nurses and physicians be closely acquainted with the prevailing traditions and religious beliefs in the communities where they serve. 20 Chinese traditional culture holds that physical death is not the end of the bearing of responsibility, and that experience should be passed down from generation to generation. Our study also showed that the vast majority of patients were worried about their loved ones suffering excessive grief at their death, which could affect their families' lives.…”
Section: Discussionmentioning
confidence: 99%